PERAN STRATEGIS KOPERASI DALAM MENINGKATKAN KEMANDIRIAN EKONOMI MASYARAKAT DESA DI KABUPATEN OGAN KOMERING ULU - Hermawati, Lisa; Pusvita, Ema; Gribaldi, Gribaldi; Mukhlis, Mukhlis; Rahayu, Sri (Fakultas Pertanian Universitas Mataram, 2025)
This study aimed to analyze the strategic role of village cooperatives, particularly the Merah Putih Cooperative, in enhancing rural community economic independence in Ogan Komering Ulu (OKU) Regency. Rural economic independence was considered a crucial issue in rural development, as it reflected the ability of rural communities to meet their economic needs independently and sustainably. This study focused on examining the effects of cooperative member participation, cooperative financial services, and cooperative education and training on rural community economic independence. This research employed a quantitative approach using a survey method. Primary data were collected through the distribution of Likert-scale questionnaires to 50 respondents, who were selected from a population of 158 active cooperative members using a purposive sampling technique. Data were analyzed using multiple linear regression analysis with the assistance of SPSS software to examine the influence of the independent variables on the dependent variable. The results indicated that, simultaneously, cooperative member participation, cooperative financial services, and cooperative education and training had a significant effect on rural community economic independence. Partially, cooperative financial services and cooperative education and training had a positive and significant effect on rural community economic independence, while cooperative member participation showed a positive but statistically insignificant effect. These findings suggested that strengthening cooperative financial services and improving human resource capacity through education and training were key factors in enhancing rural community economic independence through cooperatives.